2009
DOI: 10.1042/bj20081847
|View full text |Cite
|
Sign up to set email alerts
|

Calreticulin, a multi-process calcium-buffering chaperone of the endoplasmic reticulum

Abstract: Calreticulin is an ER (endoplasmic reticulum) luminal Ca2+-buffering chaperone. The protein is involved in regulation of intracellular Ca2+ homoeostasis and ER Ca2+ capacity. The protein impacts on store-operated Ca2+ influx and influences Ca2+-dependent transcriptional pathways during embryonic development. Calreticulin is also involved in the folding of newly synthesized proteins and glycoproteins and, together with calnexin (an integral ER membrane chaperone similar to calreticulin) and ERp57 [ER protein of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
549
1
10

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 635 publications
(572 citation statements)
references
References 186 publications
12
549
1
10
Order By: Relevance
“…All seven ER-localized chaperones and folding proteins identified are known UPR inducible proteins, suggesting the presence of ER stresses and the activation of UPR during prolonged CHO culturing. As components of the calnexin/calreticulin ER chaperone system, calreticulin and ER protein 60 (ERp60) interact and promote the proper folding of glycoproteins (Michalak et al 2009). Moreover, their roles in apoptosis have also been characterized.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All seven ER-localized chaperones and folding proteins identified are known UPR inducible proteins, suggesting the presence of ER stresses and the activation of UPR during prolonged CHO culturing. As components of the calnexin/calreticulin ER chaperone system, calreticulin and ER protein 60 (ERp60) interact and promote the proper folding of glycoproteins (Michalak et al 2009). Moreover, their roles in apoptosis have also been characterized.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, their roles in apoptosis have also been characterized. The localization and exposure of calreticulin to cell surface during apoptosis serves as a signal for the phagocytotic engulfment of cells (Michalak et al 2009). ERp60, which folds the mitochondrial calcium-dependent neutral cysteine protease l-calpain, is responsible for the cleavage and release of membrane bound apoptosis inducing factor (AIF) into the intermembrane space of mitochondria in preparation for subsequent release into the cytosol during apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…Because this biological function was independent of PR3 enzymatic activity (5), it was hypothesized that it might be related to new PR3 partner protein(s) such as CRT. CRT is well-known as a calcium-binding chaperone protein mainly located in the endoplasmic reticulum, involved in calcium homoeostasis and in the folding of newly synthesized proteins (10). CRT also plays a role in many other biological systems, including functions outside the endoplasmic reticulum, indicating that the protein is a multiprocess molecule (29).…”
Section: Discussionmentioning
confidence: 99%
“…It is now commonly accepted that CRT, originally characterized as an endoplasmic reticulum chaperone protein (10), is also a majoreat-me signal expressed at the surface of apoptotic cells, including neutrophils (11). Accordingly, decreased CRT membrane expression reduced apoptotic cell uptake by phagocytes (12).…”
Section: G Ranulomatosis With Polyangiitis (Gpa) Formerly Calledmentioning
confidence: 99%
“…CRT is a unique endoplasmic reticulum luminal protein that participates in many cellular functions, including lectinlike chaperoning, Ca 2þ storage and signaling, regulation of gene expression, cell adhesion, wound healing, and autoimmunity (4). Many studies have shown that CRT plays an important role in regulating cell motility.…”
Section: Introductionmentioning
confidence: 99%